German Tax System: Double Taxation Avoidance Conventions, Structure And Developments - DUMITER, Florin; TURCAȘ, Florin; OPREÈš, Anca (Journal of Legal Studies, 2015)
This paper presents the fundamentals of the tax system in general, the basic elements of a tax system as well as the organization of the German tax system analysis, especially throughout the tax levy and how the taxation typology functions. This theme was chosen in order to expose the principles of German taxation system. With a tumultuous and troubled history, mainly caused by the two World Wars‟ destructions, the German state is considered the "economic locomotive" and a pillar of the European Union. Germany‟s economy is mainly driven by the automotive industry, chemical industry, telecommunications, commerce and agriculture. Of particular importance is the qualitative analysis of conventions for the avoidance of double taxation concluded by Germany; and related implications on fiscal policy. The methodology used in this paper consists of presenting literature derived theories and practical analysis of the German tax system in terms of tax legislation and the evolution of double taxation conventions concluded by Germany with different countries. After the study, the conclusions on the size of the national tax system driven by the example of the German tax system were founded.